Between social museology and the traditional museum: The case of the Murillo La Greca Museum and the 2019 Occupation Convocation - Recife, PE (Cadernos de Sociomuseologia, 2021)
The research aimed on the Murillo La Greca Museum and the 2019 Occupation Call, to analyze in the light of Social Museology how educational actions tension traditional museums to more collaborative and democratic practices. It was used authors as Mario Chagas, Glauber Guedes Ferreira Lima, Bruno Brulon, Marcele Pereira, Stránský, Tereza Scheiner e Hugues de Varine-Bohan, to stablish the theoretical references between the tensions and ruptures of the Museology through the museum space. Furthermore, other authors whose approach the museum education, sociology and anthropology composed the necessary outline to analyze the data and contextualize the object in a vast discussion about the museums in the contemporary era. Through by a participative research of an exploratory characteristic and data survey about the 2019 Occupation Summon (until March 2020) in the Murillo La Greca Museum, it was able to analyze the educational activities developed during this period and reflect on the relevance of these practices, in a context of a traditional museum, for the decolonization of the museology process and the democratization of the museum space access. Thereby, it was looking for an increase of experimentations possibilities, privileging the educational sector as the engine of new practices for the museum transformations.Key words: Social Museology, Museum Education, Traditional Museums, Democratization, Decoloniality